On the heterogeneous trade and welfare effects of GATT/WTO membership - Gabriel Felbermayr; Mario Larch; Erdal Yalçin; Yoto Yotov (Kiel Institute for the World Economy (IfW), 2020)
We build on the latest developments in the structural gravity literature to quantify the partial and general equilibrium effects of GATT/WTO membership on trade and welfare. Using an extensive database covering manufacturing trade for 186 countries over the period 1980-2016, we find that the average impact of GATT/WTO membership on trade among member counties is large, positive, and significant. We contribute to the literature by estimating country-specific estimates and find them to vary widely across the countries in our sample with poorer members benefitting more. Using these estimates, we simulate the general equilibrium effects of GATT/WTO on welfare, which are sizable and heterogeneous across members, and relatively small for non-member countries. We show that countries not experiencing positive trade effects from joining GATT/WTO can still gain in terms of welfare, due to beneficial terms-of-trade effects.
Keywords: F1; F13; F14; 330; GATT; WTO; Heterogeneous Policy Effects; Structural Gravity; Welfare